Linguistic-Political Subsidiarity: a Look at South-Tyrol - Hans Drumbl (Social Work and Society)
With its economically and politically advantageous autonomy, the province of South-Tyrol (northern Italy) has developed a society in which multilingualism plays an ever more important role. As suggested in the present contribution, a solution to some still current problems and barriers that exist between the different linguistic groups can, and indeed should, be found in the principle of subsidiarity, applied consciously, and not only encouraging and accomplishing a simple improvement of the situation. Thanks to subsidiarity, we could think about eliminating existing deficits and inequality. It is precisely with this concept in mind that, half a century ago, in an evening school for young workers and later in his parish school in Barbiana, the Italian priest Don Milani established his school for"children without a school", an experiment which gained a wide reputation in the whole of Italy and which inspired the reform of scuola media emphasising the concept of language education.